Problematizing capitalism(s): Big difference? - Peck, Jamie (Environment & Planning A, 2019)
In the article, the author examines the social science theories of Fred Block, particularly on such topics as capitalism, finance, markets, and government. Other topics include Block's opinions on Polanyian socioeconomics, his thoughts on economic diversity and capitalist transformation, as well as the universalist model of capitalism as free-market globalism.
Geography
Keywords: BLOCK; Fred L.; capitalism; finance; free enterprise; markets; social sciences; the state

Can Karl Polanyi Explain the Anthropocene? The Commodification of Nature and the Great Acceleration - Steinberg, Ted (Geographical Review, 2019)
The most important historical work on the Anthropocene to date is J. R. McNeill and Peter Engelke’s The Great Acceleration: An Environmental History of the Anthropocene since 1945 (2016). The authors argue that the Anthropocene began in 1945, not in the eighteenth century, as some scientists have proposed. They single out unintentional “human actions” as the driving force behind the significant changes in biogeochemical processes unfolding since the middle of the twentieth century (McNeill and Engelke 2016, 4, 208). The main title of their book mimics a phrase first used at a 2005 conference on the future of the planet and refers to the escalating human threats to the so-called Earth System. The title was meant to parallel Karl Polanyi’s The Great Transformation: The Political and Economic Origins of Our Time (1944). Born in 1886 in Hungary, Polanyi became one of the world’s greatest economic historians. In an endnote to their book, McNeill and Engelke explain that Polanyi saw the “market economy” as a recent invention that “must be understood as embedded in social traditions, customs, and habits of the mind.” Likewise, they continue, human impacts on global ecology “are embedded in societies and their traditions” (McNeill and Engelke 2016, 213).
Geography
Keywords: ENGELKE; Peter; Great Acceleration: An Environmental History of the Anthropocene Since 1945; The (Book); MCNEILL; J. R.; anthropocene epoch; capitalism; globalization; nonfiction; urban development

Postneoliberalism as institutional recalibration: Reading Polanyi through Argentina’s soy boom - Berndt, Christian; Werner, Marion; Fernández, Víctor Ramiro (Environment and Planning A: Economy and Space, 2019)
While postneoliberalism is often interpreted as a societal reaction against the deleterious effects of marketization in Latin America, this paper develops a finer-grained Polanyian institutional analysis to gain better analytical purchase on the ambivalent outcomes of postneoliberal reforms. Drawing on recent insights in economic geography, and in dialogue with the Latin American structuralist tradition, we elaborate our framework through a case study of the Argentinian soy boom of the 2000s, identifying forms of market extension, redistribution, reciprocity and householding that facilitated this process. We argue for a multi-scalar approach that balances attention to national and extra-local dynamics shaping the combination of these forms, identified through the lens of the “fictitious commodities” of the soy boom: money (credit, currency and cross-border capital flows), land (in the agricultural heartland and frontier regions), labor (transformed and excluded in a “farming without farmers” model) and, we add, knowledge (biotech). Our analysis identifies internal tensions as well as overt resistance and “overflow” that ultimately led to the collapse of postneoliberal regulation of the soy complex, ushering in a wider, market-radical counter-movement. Refracting double-movement-type dynamics through the prism of heterodox institutional forms, we argue, allows for a better grasp of processes that underlie institutional recalibrations of progressive and regressive kinds.
Geography
Keywords: Argentina; Polanyi; institutions; marketization; post-neoliberalism; soy; uneven development

Economic and Political Foundations of Effective Transition to Renewable Energy: Ordoliberalism, Polanyi, and Cities as Hubs for Climate Leadership and Innovation - Lysack, Mishka (Renewable Energy: International Perspectives on Sustainability, 2019)
A remarkable transition to a renewable energy economy (also known as the Energiewende) with ambitious climate protection and sustainable economic development is taking place in Germany, with many German cities exemplifying best practices in effective climate leadership to attain ambitious climate goals, such as Munich (1.4 million) moving steadily to its targets of 100% renewable energy by 2025 and 100% renewable heat by 2040. Similarly, the former coal city of Bottrop in West Germany won the Innovation Ruhr Prize for increasing its refurbishment rate to 3% (3× national average), installing solar panels, reducing its GHG emissions by 37%, and attracting over $316 million in economic investment in sustainability. However, it needs to be noted these accomplishments do not take place in a vacuum, but within a supportive and empowering policy and economic context which includes two key elements. The first entails using Karl Polanyi’s three key analytic resources of restoring the social and environmental dimensions of the economy: (1) re-embedding the economy within society and in turn, within the larger context of the environment, (2) reversing the reduction of labour and land into “fictitious commodities” and tradable goods; and (3) fostering the “double movements” of the protective responses of both government and society to correct the negative impacts of the free-market economy. Secondly, the economic approach of ordo-liberalism in Germany facilitates the shift to an economy with economic rules and “referees,” fostering the renewable energy transition through innovative economic and social capital approaches, while also deconstructing the economic monopolies and concentrations of political-economic power that arise in neo-liberal and authoritarian economies.
Political Science; Geography
Keywords: double movement; fictitious commodities; ordoliberalism; reembedding; renewable energy economy; sustainability